How long should we continue crizotinib in ALK translocation-positive inflammatory myofibroblastic tumors? Long-term complete response with crizotinib and review of the literature. (June 2020) - Alan, Ozkan; Kuzhan, Okan; Koca, Sinan; Telli, Tugba Akin; Basoglu, Tugba; Ercelep, Ozlem; Filinte, Deniz; Sengul, Yildiz; Arikan, Huseyin; Kaya, Serap; Babacan, Nalan Akgul; Dane, Faysal; et al.
Introduction: Inflammatory myofibroblastic tumor is a rare disease which is typically seen in children and young adults. Approximately half of the inflammatory myofibroblastic tumors contain translocations that result in over-expression of anaplastic lymphoma kinase gene. Herein, we present two anaplastic lymphoma kinase-positive cases with long-term remission with crizotinib. We do not know how long these therapies need to be continued. Case reports: We present two cases of inflammatory myofibroblastic tumor treated with anaplastic lymphoma kinase inhibitor therapies: an 8-year-old Turkish boy and a 21-year-old Caucasian man. Management and outcome: Two cases, both with good tumor control under crizotinib, but one who progressed on drug holiday, responded again to the same drug, and had a very short period of response after restarting crizotinib. Conclusion: A molecular-targeted drug (anaplastic lymphoma kinase inhibitor) was found to be extremely effective as selective therapy for inflammatory myofibroblastic tumor with anaplastic lymphoma kinase translocation. Here, we want to emphasize the continuation of this treatment after achieving a good response until progression or a major side effect.